Older sex offenders – managing risk in the community from a policing perspective - Bows, Hannah (Policing and society, 2018)
Although there has been an increase in research and policy attention examining sex offenders, their motivations and how ‘risk’ should be managed in relation to registered sex offenders in the community, the majority of these efforts have concentrated on young offenders. This paper presents the findings from a qualitative study involving interviews with offender managers working in six forces across England and Wales. The study produced a number of key findings: (1) there is an increasing number of older sex offenders subject to offender management and these offenders have particular needs; (2) there are a number of specific challenges in managing older offenders and (3) these create a number of a specific issues when managing older offenders with care or support needs. Implications for those involved in the management of sex offenders are discussed and best practice highlighted.